Elacatinus janssi, a new gobiid fish from Costa Rica - Bussing, William A. (1981)
A new seven-spined goby, Elacatinus janssi, is described from 203 specimens collected at thirteen localities along the Pacific coast of Costa Rica. It is distinguished from its congeners and compared to a similar western Atlantic species.